Implementasi Pembelajaran Matematika menggunakan Komik dalam Pembelajaran Jarak Jauh - Rita Yuningsih; Yusnawati Yusnawati; Ayu Desran; Suci Ramadhanti Febriani; Bedra Guettaoui (PAKAR Pendidikan, 2022)
Distance learning requires teachers to innovate in learning system.This study aims to analyze mathematics learning using comics for distance learning (PJJ) media in terms of planning, implementation and evaluation in learning. This study uses a qualitative research design with the method used is a case study. The data collection techniques include observations in the learning class, documentation on the implementation of learning plans and interviews with teachers and students of class VII who are used as research samples. The analysis technique uses a data source triangulation design. The results showed that the learning process using comics had a positive impact on students and teachers, it was marked by an increase in teacher creativity, increase in student learning outcomes by 53%, the development of learning motivation and the high enthusiasm of students in studying comics as a distance learning teaching medium. The research findings indicate that the creativity of teachers in managing the learning process is able to provide an active learning situation. This study recommends further research in order to examine various learning topics with more complex methods.